Evaluation of corneal biomechanical behavior in vivo for healthy and keratoconic eyes using the stress–strain index. Issue 10 (October 2022) - Padmanabhan, Prema; Lopes, Bernardo T.; Eliasy, Ashkan; Abass, Ahmed; Vinciguerra, Riccardo; Vinciguerra, Paolo; Ambrósio, Renato; Elsheikh, Ahmed
Abstract : The stress–strain index deteriorates with keratoconus progression. Owing to the focal nature of the disease, no statistically significant difference was observed between healthy individuals and early cases. Abstract : Purpose: To evaluate the characteristics of corneal material properties in healthy individuals and keratoconic patients using the stress–strain index (SSI). Setting: Vincieye Clinic in Milan, Italy, and Instituto de Olhos Renato Ambrósio in Rio de Janeiro, Brazil. Design: Retrospective observational cross-sectional study. Methods: Records of 1221 patients were divided into 3 groups: healthy corneas (n = 728), bilateral keratoconus (KC, n = 388), and very asymmetric ectasia (VAE, n = 105) when patients presented with clinical ectasia in 1 eye and normal topography (VAE-NT) in the fellow eye. All patients were examined with Pentacam HR and Corvis ST. Severity of KC cases was stratified according to the Pentacam topographic KC classification. The SSI distribution across the different groups and its correlation with age, biomechanically corrected intraocular pressure (bIOP), and central corneal thickness (CCT) were assessed. Results: A statistically significant difference between healthy individuals and each of the keratoconic groups ( P < .001) was observed, and a progressive reduction in the SSI was observed across the groups. A significant correlation was observed between the SSI and age in all groups ( P < .010) but KC severe subgroup ( P = .361). No correlation between the SSI and bIOP and CCT was observed in all KC subgroups and VAE-NT groups ( P > .050). Among healthy eyes, there was only a mild correlation between the SSI and bIOP ( R = 0.12, P = .002) and CCT ( R = 0.13, P = .001). Conclusions: This study estimates the in vivo corneal material properties in healthy individuals and patients with KC using a new method. The SSI showed a progressive deterioration within the advance in disease stages while being relatively independent of bIOP and CCT but positively correlated with age.